2015
DOI: 10.1007/s11205-015-1005-7
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity, Sedentary Behaviors and Subjective Well-Being in Older Adults: An Eight-Year Longitudinal Research

Abstract: This study aimed to assess the independent and prospective associations of aspects of self-reported leisure-time physical activity (LTPA) and leisure-time sedentary behaviors (LTSB) with subjective well-being (SWB). Data from the 1999Data from the , 2003Data from the , and 2007 phases of the Survey of Health and Living Status of the Elderly conducted by the Taiwan Ministry of Health and Welfare on a nationally representative sample of older Taiwanese were used. A fixed cohort of 1268 participants aged 70 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 58 publications
9
52
2
9
Order By: Relevance
“…For the very first time, they showed that this relation was mediated via frequency of leisure activity participation. Empirically, this is in line with studies showing that health limitations in old age are related to reduced participation in physical, intellectual, and social activities [15][16][17][18] and that such restrictions in activity engagement are related to lower wellbeing in old age [19][20][21] .…”
Section: Introductionsupporting
confidence: 86%
“…For the very first time, they showed that this relation was mediated via frequency of leisure activity participation. Empirically, this is in line with studies showing that health limitations in old age are related to reduced participation in physical, intellectual, and social activities [15][16][17][18] and that such restrictions in activity engagement are related to lower wellbeing in old age [19][20][21] .…”
Section: Introductionsupporting
confidence: 86%
“…Los resultados de este estudio indican que, efectivamente, todas las dimensiones de la satisfacción experimentada en contextos específicos se relacionan fuertemente con la satisfacción con la vida. Estudios anteriores habían mostrado ya una relación entre la satisfacción con la vida y la satisfacción con uno mismo (Rittenour & Colaner, 2012), con la resiliencia (StackCutler, Parrila & Torppa, 2015), con los estudios (Flynn & Macleod, 2015) y con el tiempo de ocio (Ku, Fox & Chen, 2016). Nuestro estudio, sin embargo es el primero que investiga la relativa aportación de cada una de estas áreas en la satisfacción con la vida de los adolescentes.…”
Section: Discussionunclassified
“…Embora seja consensual que o que o comportamento sedentário é definido por gastos energéticos ≤1.5 equivalentes metabólicos (METs) quando se está na posição sentada ou reclinada Tremblay, Colley, Saunders, Healy, & Owen, 2010), os estudos que examinaram as consequências do tempo sedentário na saúde psicossocial dos idosos utilizaram diferentes definições operacionais (Balboa-Castillo, León-Muñoz, Graciani, Rodríguez-Artalejo, & Guallar-Castillón, 2011;Hamer & Stamatakis, 2014;Gardner, Lliffe, Fox, Jefferis, & Hamer, 2014;Rosenberg et al, 2016;Ku, Fox, & Chen, 2016a). Nesse sentido, é sugerido que os estudos possam utilizar definições padronizadas acerca do tempo sedentário, baseadas em teorias ou em evidências .…”
Section: Estudos Em Saúde Psicossocial Com a População Idosaunclassified
“…Desta forma, os resultados sugeriram que as mudanças diárias no tempo sedentário e no nível de atividade física têm implicações na satisfação com a vida dos idosos (Maher & Conroy, 2015). Contundo, o estudo longitudinal de Ku et al (2016a) investigou as associações entre o tempo sedentário e a satisfação com a vida de 1268 idosos, através da Life Index A (LSLA). Foi evidenciado que determinados comportamentos sedentários (e.g., ver TV, ler, conversar socialmente) estavam positivamente associados à satisfação com a vida dos idosos.…”
Section: Qualidade De Vidaunclassified
See 1 more Smart Citation